Digital thermometer / Muhammad Shawwal Mohamad Rawi and Zahirwan Zaidi - Mohamad Rawi, Muhammad Shawwal; Zaidi, Zahirwan (2003)
Digital thermometer is often necessary to measure the temperature of liquids or heat conditional in an oven. This digital thermometer using 4 segment display like for output where is quite accurate for temperature from -40 to -100. Body of this project,making by sheet metal gauge aluminum or black pfaaic box and its body havn on/off switch and hole for ic heat for any alteration of heat for vicinity. The ail reading very exactly some for manual thermometer when to differ its orders. When, the measure some temperature , sensor take some minutes to detect correct temperature where surrounding temperature between 25 degree